Early neurodevelopmental outcomes of congenital gastrointestinal surgical conditions: a single-centre retrospective study - Max K Bulsara; Karen Simmer; Sanjay Patole; Vamsi Batta; Shripada Rao; Deepika Wagh; Jason Khay Ghim Tan; Ian Gollow (BMJ Paediatrics Open)
Background Evidence is emerging that surgery in the neonatal period is associated with increased risk of suboptimal neurodevelopmental outcomes (SNDO). The aim of this study was to describe neurodevelopmental outcomes (at 1 year) of neonatal surgery for congenital gastrointestinal surgical conditions (CGSC) and to explore risk factors.Methods Retrospective study (2005–2014) of infants born ≥34 weeks gestation with CGSC and admitted to the surgical neonatal intensive care unit of Perth Children’s Hospital, Western Australia. Clinical details and 1-year developmental outcomes based on Griffiths Mental Developmental Assessment Scales were collated from the database and by reviewing the medical records of study infants. SNDO was defined as one or more of the following: a general quotient less than 88 (ie, >1 SD below mean), cerebral palsy, blindness or sensorineural deafness. Univariable and multivariable logistic regression analyses were carried out to explore risk factors for SNDO. A total of 413 infants were included, of which 13 died. Median gestation was 37.6 weeks (IQR: 36.4–39.1). Information on developmental outcomes was available from 262 out of 400 survivors. A total of 43/262 (16.4%) had SNDO. On univariable analysis, lower z scores for birth weight, prolonged duration of antibiotics, increased episodes of general anaesthesia and prolonged duration of hospital stay were associated with SNDO. On multivariable analysis, lower z scores for birth weight and prolonged hospital stay were associated with increased risk of SNDO.Conclusions Late preterm and term infants undergoing neonatal surgery for CGSC may be at risk for SNDO. Studies with longer duration of follow-up are needed to further evaluate the role of potentially modifiable risk factors on their neurodevelopmental outcomes.